Experimental and Numerical Investigations into the Influence of the Process Parameters During the Deep Drawing of Fiber Metal Laminates - Heggemann, Thomas; Sapli, Hüseyin; Homberg, W. (Forming the Future)

Improving the Accuracy of Deep Drawn Fiber-Metal Laminate Parts by Preliminary Surface Treatment - Voswinkel, Dietrich; Sapli, Hüseyin; Kloidt, Dennis; Heggemann, Thomas; Homberg, Werner; Grydin, Olexandr; Schaper, Mirko (IOP Conference Series: Materials Science and Engineering)

Joining with Friction Spun Joint Connectors – Manufacturing and Analysis - Wischer, Christian; Steinfelder, Christian; Homberg, Werner; Brosius, Alexander (IOP Conference Series: Materials Science and Engineering)
Nowadays, the production of modern lightweight structures, like a body in white structure requires a wide variety of mechanical joining processes. To fulfill the various demands, mechanical joining processes and joining elements (JE) are used. Very often, they are adapted to the application, which leads in turn to a numerous of different variants, high costs, and loss of the process chain versatility. To overcome this drawback, an innovative approach is the usage of individually produced and task-adapted JE, the so-called friction spun joint connectors (FSJC). These connectors can be modified in shape as well as in material properties. This flexibility offers high potential for lightweight design but also increases the necessary analytical effort regarding the forming process as well as the manufactured joint's properties. Therefore, a new analysis strategy based on the Finite-Element-Method (FEM) is proposed, which numerically determines the local load bearing capacity within a given joint in order to identify the critical regions for load transfer. The process of joining element manufacturing and the analysis strategy will be described in detail and optimization results of the joints are shown. Numerical results are discussed and possible recommendations for joint manufacturing are derived.

A contribution on versatile process chains: joining with adaptive joining elements, formed by friction spinning - Wischer, Christian; Homberg, Werner (Production Engineering)

Model approaches for closed-loop property control for flow forming - Riepold, Markus; Arian, Bahman; Vasquez, Julian Rozo; Homberg, Werner; Walther, Frank; Trächtler, Ansgar (Advances in Industrial and Manufacturing Engineering)
The implementation of control systems in metal forming processes improves product quality and productivity. By controlling workpiece properties during the process, beneficial effects caused by forming can be exploited and integrated in the product design. The overall goal of this investigation is to produce tailored tubular parts with a defined locally graded microstructure by means of reverse flow forming. For this purpose, the proposed system aims to control both the desired geometry of the workpiece and additionally the formation of strain-induced α′-martensite content in the metastable austenitic stainless steel AISI 304 L. The paper introduces an overall control scheme, a geometry model for describing the process and changes in the dimensions of the workpiece, as well as a material model for the process-induced formation of martensite, providing equations based on empirical data. Moreover, measurement systems providing a closed feedback loop are presented, including a novel softsensor for in-situ measurements of the martensite content.

Friction-Induced Recycling Process for User-Specific Semi-Finished Product Production - Borgert, Thomas; Homberg, Werner (Metals)
Modern forming processes often allow today the efficient production of complex parts. In order to increase the sustainability of forming processes it would be favorable if the forming of workpieces becomes possible using production waste. At the Chair of Forming and Machining Technology of the Paderborn University (LUF) research is presently conducted with the overall goal to produce workpieces directly from secondary aluminum (e.g., powder and chips). Therefore, friction-based forming processes like friction spinning (or cognate processes) are used due to their high efficiency. As a pre-step, the production of semi-finished parts was the subject of accorded research work at the LUF. Therefore, a friction-based hot extrusion process was used for the full recycling or rework of aluminum chips into profiles. Investigations of the recycled semi-finished products show that they are comparable to conventionally produced semi-finished products in terms of dimensional stability and shape accuracy. An analysis of the mechanical properties of hardness and tensile strength shows that a final product with good and homogeneously distributed properties can be produced. Furthermore, significant correlations to the friction spinning process could be found that are useful for the above-mentioned direct part production from secondary aluminum.

Cutting Blades for Food Processing Applications Manufactured Using Innovative Spin Forming - Rostek, Tim; Makeieva, Hanna; Homberg, Werner (Proceedings of the 13th International Conference on the Technology of Plasticity)

Investigations and Improvements in 3D-DIC Optical Residual Stress Analysis—A New Temperature Compensation Method - Dahms, Frederik; Homberg, Werner (Forming the Future)

Magnetic Barkhausen noise analysis for microstructural effects separation during flow forming of metastable austenite 304L. - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Walther, Frank; Homberg, Werner; Trächtler, Ansgar (Proceedings of the 11th International Workshop NDT in Progress)

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

Forming of Parts with Locally Defined Mechanical and Ferromagnetic Properties by Flow-Forming - Wiens, Eugen; Homberg, Werner; Arian, Bahman; Möhring, Kerstin; Walther, Frank (Forming the Future)

Joining with versatile joining elements formed by friction spinning - Wischer, Christian; Wiens, Eugen; Homberg, Werner (Journal of Advanced Joining Processes)

Development of a novel adaptive joining technology employing Friction-Spun Joint Connectors (FSJC)

Combined Curing and Forming of Fiber Metal Laminates - Heggemann, Thomas; Homberg, Werner; Sapli, Hüseyin (Procedia Manufacturing)

Combined Curing and Deep Drawing of Fiber Metal Laminates to Spherical Hybrid Components - Sapli, Hüseyin; Heggemann, Thomas; Homberg, Werner

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

Joining with Versatile Friction-Spun Joint Connectors - Rostek, Tim; Wiens, Eugen; Homberg, Werner (Procedia Manufacturing)

Some ideas for the further development of hydroforming process chains - Wiens, Eugen; Djakow, Eugen; Homberg, Werner (Nebu/Nehy 2020)
Even though the spectrum of parts is expected to shift over the long term as a result of increasing e-mobility, there is still an extremely high demand for complex components made of high-strength materials which can only be produced by hydroforming technologies. The innovative combination of hydroforming processes with other forming processes, as well as the improvement of the processes themselves, offers considerable potential for improvement. A number of promising ways of improving the hydroforming process chain are therefore the subject of this contribution. The focus of the article is on possible approaches for combining (incremental) pre- and post-forming operations, which can permit considerable improvements in both quality and features at a reduced cost. Furthermore, a novel combination of quasi-static and high-speed forming processes is presented, leading to an improved overall forming process (with a high application potential) for the production of complex parts.
Keywords: Hydroforming; Incremental Forming; Internal Flow-turning; High-speed Forming

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Intrinsically lubricated tool inserts for deep drawing applications generated by selective laser melting - Bader, Fabian; Hengsbach, Florian; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)
Abstract. Within the scope of this study, an intrinsically lubricated deep drawing die fabricated via laser beam melting (LBM) is investigated. In contrast to the common objective of generating highly dense LBM components, this work endeavors to achieve intended micro-scale porosity. By utilizing permeable structures, in-process closed-loop control of lubrication during the forming operations is feasible. Based on a modified AM scan strategy, the required filigree, porous structures can be generated. Thus, in the present work three permeable specimens are additively generated from the maraging steel 1.2709. The cylindrical specimens are then analyzed via light microscopy (LM), microcomputer tomography (microCT), and with regard to the oil throughput rate. Subsequently, an intrinsically lubricated, AM deep drawing tool die is manufactured and experimentally tested. The findings reveal interesting results for deep drawn specimens with AM deep drawing dies.